Aeromonas caviae alters the activities of ecto-enzymes that hydrolyze adenine nucleotides in fish thrombocytes. (February 2018) - Baldissera, Matheus D.; Souza, Carine F.; Verdi, Camila M.; Vizzotto, Bruno S.; Santos, Roberto C.V.; Baldisserotto, Bernardo
Abstract: It is recognized that the purinergic system, through the activities of ectonucleoside triphosphate diphosphohydrolase (E-NTPDase), ecto-5′-nucleotidase (E-5′-nucleotidase), and ecto-adenosine deaminase (E-ADA), is involved in the regulation and modulation of the physiological and pathological events linked to hemostasis. This occurs due to the role of adenosine diphosphate (ADP) in the activation and recruitment of platelets, and the role of adenosine (Ado) in the inhibition of platelet activation. Thus, here we aimed to evaluate whether Aeromonas caviae infection impairs the ecto-enzymes of the purinergic system in fish thrombocytes and the involvement of this system in the hemorrhagic septicemia. The total number of fish thrombocytes decreased in infected animals compared to uninfected animals. Regarding the ecto-enzymes of the purinergic system, the E-NTPDase and E-5′-nucleotidase activities increased in infected animals compared to uninfected animals, while the E-ADA activity decreased. These findings show that adenine nucleotide hydrolysis is modified in the thrombocytes of fish experimentally infected with A. caviae, which impairs the coagulation process due the excessive hydrolysis of ADP, a molecule linked with activation and recruitment of thrombocytes at the site of vascular injury, and augmentation on Ado levels, a molecule linked with inhibitory effects on platelet activation and aggregation. In summary, the purinergic system might contribute to the occurrence of hemorrhagic frames in fish infected with A. caviae. Highlights: Purinergic system exerts important role in events linked to hemostasis. Aeromonas caviae infection alter the activities of ecto-enzymes in fish thrombocytes. These alterations might contribute to the occurrence of hemorrhagic frames.